Evaluation of bowl sludges as a source of phosphorus nutrient for Hevea brasiliensis - George E S; Karthikakutyamma M; Punnoose K I (Natural Rubber Research, 2005)
Field experiments conducted at two locations in Kerala, India to evaluate bowl sludge, a waste product from latex centrifuge factories, revealed its usefulness as a source of phosphorus nutrient for rubber (Hevea brasiliensis). The increment in girth and yield was comparable to that when super phosphate or mussoorie rock phosphate was used. Soil chemical properties were not affected by continued application though bowl sludge contained appreciable quantity of magnesium. Leaf and latex nutrient contents were also unaffected. The result of the study indicated bowl sludge as a potential source of phosphorus fertilizer for rubber plantations.
Keywords: Bowl sludge; Bowl sludge; Phosphatic fertilizers; Phosphatic fertilizers; Waste utilization; Waste utilization